Integrated influential factors of internal stakeholder that negatively affecting project successful completion in Yemen - AL-Fadhali,, Najib; Ng, Kim-Soon; Zainal, Rozlin; Ahmad, Abd Rahman; Ali Hasaballah, Abdel Hafiez (Medwell Journals, 2018)
Development construction projects in Yemen are encountering a huge delays in time, cost invade, surrendered and disappointment. Because of an emotional movement in the limit and volume of the Yemeni development part in the course of the most recent decade, the need of a deliberate investigation of the reasons that adversely influencing negatively the project successful completion and building up an unmistakable comprehension among the stakeholder experts is profoundly urgent. The fundamental objective of this study is to recognize and rank the causes that contrarily influencing the project successful completion in Yemen. Utilizing a chose set of 55 qualities, this exploration initially distinguished the key elements affecting project completion in Yemen development industry. A survey has framed the premise of this examination and dispersed to proprietor, advisor and temporary worker. The outcome covers that the 10 major delay factors including money cash flow and financial difficulties faced by contractors, conflict between owners and other parties, delay in progress payment by owner, poor project management, slow decision from owner, escalation of prices of materials, lack of contractor experience, design errors made by designers, shortages of materials and poor site management and supervision. These findings are expected to be significant contributions to Yemen construction industry in controlling the time and cost overruns in construction. The effect of (IIF) is negatively influences to project successful completion regarding to time overrun, cost overrun, negatively affect to satisfaction of the stakeholder, negatively affect to technical specification and negatively affecting to fulfillment all meeting all the project objectives/requirements. These findings are required to be noteworthy commitments to Yemen development industry in controlling the time and cost invades in development.